Cultural Symbolism and Spatial Separation: Some Ways to Deactivate Exclusionary Responses to Culture Mixing. (November 2016) - Yang, Daniel Y.-J.; Chen, Xia; Xu, Jing; Preston, Jesse L.; Chiu, Chi-yue
When and why do local communities display negative or exclusionary responses to mixing and blending of local and foreign cultural symbols in the same space or percept? Results from three experiments showed that the local community reacted most negatively to culture mixing when both objects were perceived to be icons or symbols of their culture of origin (Experiments 1-3). Experiment 3 further shows that concern about cultural contamination underlies exclusionary responses to culture mixing. We also identified two conditions that can deactivate such responses. First, even when the cultural symbols were presented simultaneously, keeping a distance between them assuages the concern over cultural contamination (Experiment 3) and reduces the perceivers' negativity to culture mixing (Experiments 1-3). Second, not attributing cultural symbolism to either cultural object also makes exclusionary responses less likely (Experiments 1-3). These effects were observed among Americans (Experiments 1 and 2) and Chinese (Experiment 3) and across three different examples of culture mixing.